MILITARY SPHERE IN THE BUKHARA KHANATE (XVI-XVIII CENTURIES) - Yuldashev Furqat Bekturdiyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article briefly covers the military sphere and socio-political situation in the Bukhara Khanate in the XVI-XVIII centuries.